Stem Cells in Cancer: Should We Believe or Not? - Grande, Enrique; Antón Aparicio, Luis (Springer Netherlands : Imprint: Springer, 2014)
This volume explores the latest developments in a novel area of molecular biology and a hot topic in the field of oncology: cancer stem cells. These chapters from expert contributing authors present concepts such as the universal stem cell, new molecular pathways, new targeted agents, the different roles that cancer stem cells seem to have according to the organ they are placed in, and the future role that targeting cancer stem cells may have in the management of patients in the clinic.    Exploring the latest research including new data from randomized trials, this book examines important proposals over the origin of cancer stem cells such as the possibility that cancer stem cells may arise from mutated stem cells or a fully differentiated cell that may undergo several mutations that drive it back to a stem-like state. The authors consider the role that stem cells seem to have in the onset, development and resistance to classical antitumoral treatments of cancer and discuss possible potential future treatment modalities for the management of advanced cancer patients.  The question, "Are stem cells involved in cancer?" may not have a simple answer, but ongoing investigations, in-depth consideration and a broad spectrum of information can be found in this book, allowing the reader to arrive at his or her own answer.   This book will appeal to researchers in the field of oncology and cancer research and biomedical scientists with an interest in stem cells.